Optimal velocity profiles for vault - van der Eb, J.; Filius, M.; Rougoor, G.; Van Niel, C.; de Water, J.; Coolen, B.; de Koning, H. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
The aim of this study was to determine which kinematic characteristics may be used as a performance indicator(s) for vault. Over 600 vaults (299 men and 216 Women, see Table 1) were recorded and analyzed using footage of 3 high-speed cameras taken at the 2010 Rotterdam Artistic Gymnastics World Championships. The kinematics were correlated with the judge`s outcome score: type of vault, difficulty and final score. The correlation coefficients between velocity at takeoff and final judges` scores were r = 0.60 for men and r = 0.52 for women.